The Influence of Entrepreneurship Knowledge, Motivation and Family Environment on Entrepreneurship Interest - Qodariah, Qodariah; Arifin, Yodhi Adytia (Ridwan Institute, 2023)
This research focuses on understanding the entrepreneurial interest of MSME players in Paninggilan Utara Urban Village, Tangerang City, which is influenced by family environment, motivation, and entrepreneurial knowledge. The total population implemented in the research is 150 subjects while the number of samples implemented in the research is 110 actors determined based on random sampling techniques. The analysis technique in the research applies multiple linear regression tests using the help of SPSS type 25 software and Microsoft Excel 2016. Based on the research conducted, it is found that there is a significant positive influence between the family environment, motivation, and entrepreneurial knowledge with entrepreneurial interest. The researcher hopes that the research can be used as a reference to improve the quality and quantity of MSME players in Paninggilan Utara Village, Tangerang City.